UPAYA MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI BERMAIN LOGICO - Rusmiati Rusmiati; Anis Husni Firdaus (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Early childhood is a child in the age range of 0-6 years who is experiencing growth and development so that proper stimulation is needed in order to grow and develop optimally. Cognitive development in early childhood is very important so that children are able to explore the world around them. Through cognitive development, the function of thinking can be used quickly and precisely in overcoming a problem in overcoming a problem. Through learning games, it will be fun and can be absorbed by the child optimally. The purpose of this study was to determine the learning process using logico playing media in an effort to improve cognitive development of early childhood group B TPA Al-Falah, Cijeungjing District, Ciamis Regency through Logico games. A game that uses a Logico board with question sheets. The research method used is classroom action research using a research model by Jhon Elliot. The research subjects were group B students (ages 4-5 years) for the 2019/2020 TPA Al-Falah TPA, Cijeungjing District, Ciamis Regency, totaling 10 children. In this classroom action research, the object of research is an effort to improve early childhood cognitive development through the game Logico in group B. The data collection methods used are observation, interviews and documentation. The instruments used were development assessment instruments, research instruments, observation. This Classroom Action Research was conducted in three cycles and each cycle had one meeting. The results of the study prove that playing Logico can improve early childhood cognitive development, as evidenced by seeing the results of calculations in every aspect of the observation that has increased in each cycle. The results of cognitive development at the pre-cycle play stage showed 32.5% while the first cycle increased by 42% in the second cycle it increased again to 55% while in the third cycle it increased to 75%. In the Logico game to improve early childhood cognitive development, a teacher is recommended to prepare things that support the implementation of the game such as interesting games according to the child's needs.